Structure of an innexin gap junction channel and cryo-EM sample preparation. (21st September 2017) - Oshima, Atsunori
Abstract : An atomic structure of the Caenorhabditis elegans innexin-6 gap junction channel has recently been determined using single-particle cryo-electron microscopy. This review summarizes progress toward determining the innexin-6 gap junction channel structure and essential tips for preparing cryo-electron microscopy samples for high-resolution structural analysis of an innexin gap junction channel. Abstract: Gap junction channels are essential for mediating intercellular communication in most multicellular organisms. Two gene families encode gap junction channels, innexin and connexin. Although the sequence similarity between these two families based on bioinformatics is not conclusively determined, the gap junction channels encoded by these two gene families are structurally and functionally analogous. We recently reported an atomic structure of an invertebrate innexin gap junction channel using single-particle cryo-electron microscopy. Our findings revealed that connexin and innexin families share several structural properties with regard to their monomeric and oligomeric structures, while simultaneously suggesting a diversity of gap junction channels in nature. This review summarizes cutting-edge progress toward determining an innexin gap junction channel structure, as well as essential tips for preparing cryo-electron microscopy samples for high-resolution structural analysis of an innexin gap junction channel.